AIR POLLUTION BY ROADSIDE DUST AND AUTOMOBILE EXHAUST AT BUSY ROAD-CROSSINGS OF LAHORE - Jafary, Zafar Altaf; Faridi, Ilyas Ahmed (Pakistan Journal of Physiology, 2006)
Background: Lahore is one of the most polluted metropolis of Pakistan and only a few studies have been conducted in this country so far, for the assessment of pollution levels prevalent in relation to the ever increasing roadside automobile traffic. This study was carried out to assess the roadside dust and autoexhaust gaseous levels at 23 busy road-crossings of Lahore. Methods: The roadside dust levels were determined by using ‘High volume portable dust sampler’ and autoexhaust gaseous levels were estimated by using ‘Drager tubes’ for Carbon monoxide, Sulphur dioxide and Nitrogen dioxide gases with ‘Drager suction pump’. Results: Twenty three sites were sampled for dust and gaseous level estimation. Out of all these; dust concentration was <1.5 mg/m3/hr at 8 (35%) sites, between 1.5-3.0 mg/m3/hr at 9 (39%) sites and >3.0 mg/m3/hr at 6 (26%) sites. Regarding gaseous levels, more than 7 (30%) sites had Carbon monoxide level in excess of 9ppm, whereas 7 (30%) sites had sulphur dioxide level of 20ppm. Nitrogen dioxide levels were hardly above 0.20ppm or below detection limits, due to being lower than the minimum detection limit of the available nitrogen dioxide testing Drager tubes. Conclusion: The levels of roadside dust and autoexhaust gaseous pollutants present in the tested areas are quite high and this is by all means a health hazard to the public at large and inhabitants of these areas in particular. Some sort of preventive/ protective measures need to be taken to safeguard the health of the people at risk.